2017
DOI: 10.3341/kjo.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic Refraction in Hyperopic Children: Effectiveness of a 0.5% Tropicamide and 0.5% Phenylephrine Addition to 1% Cyclopentolate Regimen

Abstract: PurposeTo evaluate the effectiveness of a cycloplegic regimen using 0.5% tropicamide and 0.5% phenylephrine (Tropherine, Hanmi Pharm), in addition to 1% cyclopentolate, in hyperopic children.MethodsThe medical records of hyperopic patients below the age of 14 years who had undergone cycloplegic retinoscopy were retrospectively reviewed. Cycloplegic refractions were performed using one of two cycloplegic regimens. Regimen 1 was a Tropherine-added regimen comprising the administration of one drop of 1% cyclopent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…Cycloplegic retinoscopy reveals significantly more hyperopia than is found under non-cycloplegic conditions, in line with previous studies using pre-and post-cycloplegic autorefraction, both in children and adults, 1,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] with the mean difference reported by the present study (0.59 AE 0.51DS) similar to autorefraction values. 18,25 As found using autorefraction, the largest differences were demonstrated in the present study's youngest participants (6)(7) year-olds), with differences reducing significantly as age increased up to 12-13 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cycloplegic retinoscopy reveals significantly more hyperopia than is found under non-cycloplegic conditions, in line with previous studies using pre-and post-cycloplegic autorefraction, both in children and adults, 1,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] with the mean difference reported by the present study (0.59 AE 0.51DS) similar to autorefraction values. 18,25 As found using autorefraction, the largest differences were demonstrated in the present study's youngest participants (6)(7) year-olds), with differences reducing significantly as age increased up to 12-13 years.…”
Section: Discussionsupporting
confidence: 92%
“…Where published data are available, they tend to be limited by the use of inappropriate statistical analyses or methodologies. For example, Yoo et al . used retrospective analysis of retinoscopy results undertaken by different clinicians across an unspecified timeframe to evaluate differences between cycloplegic regimes recorded in hospital notes and failed to employ the Bland‐Altman approach to comparison analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to compare the cycloplegic effects of these agents, and different results have been reported. [7][8][9][10] In addition, cross-sectional imaging methods, including magnetic resonance imaging and Scheimpflug camera imaging, are used to determine the mechanisms underlying accommodation and cycloplegic action. [11][12][13][14] Anterior-segment optical coherence tomography (AS-OCT) has evolved rapidly for noninvasive imaging of the anterior segment of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Still, there remains no consensus as to the optimal regimen for use in children. 10,15 According to a survey of 522 pediatric ophthalmologists, the most common mixture appears to be tropicamide-cyclopentolate-phenylephrine (TCP), followed by cyclopentolate-phenylephrine (CP). 16 While many continue to recommend TCP, 15,17 the added benefit of tropicamide remains dubious.…”
mentioning
confidence: 99%
“…10,15 According to a survey of 522 pediatric ophthalmologists, the most common mixture appears to be tropicamide-cyclopentolate-phenylephrine (TCP), followed by cyclopentolate-phenylephrine (CP). 16 While many continue to recommend TCP, 15,17 the added benefit of tropicamide remains dubious. 18,19 One study found no significant difference in accommodative amplitude or pupil diameter between a TCP solution and CP control, suggesting that any effect induced by tropicamide was negligible in comparison to that of cyclopentolate and phenylephrine.…”
mentioning
confidence: 99%